2012
DOI: 10.1016/j.ijrobp.2010.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in Exhaled Nitric Oxide Predicts for Radiation Pneumonitis

Abstract: Purpose Radiation pneumonitis is a major toxicity following thoracic radiotherapy with no method available to accurately predict the individual risk. This is a prospective study to evaluate exhaled nitric oxide as a predictive biomarker for radiation pneumonitis in esophagus cancer patients. Patients and Methods 34 patients prescribed neoadjuvant chemoradiotherapy for esophagus cancer were enrolled in this trial. Each received respiratory surveys and exhaled nitric oxide (NO) measurements before, at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The results were similar to this study. The eNO-changing ratio can be used to predict the occurrence of SRP after thoracic radiotherapy, which is similar to Guerrero et al [29]. Guerrero et al studied 34 patients with esophageal cancer and found that the eNO-changing ratio can be used as a classifier to predict SRP with a smaller average error rate (only 8%).…”
Section: Discussionsupporting
confidence: 54%
“…The results were similar to this study. The eNO-changing ratio can be used to predict the occurrence of SRP after thoracic radiotherapy, which is similar to Guerrero et al [29]. Guerrero et al studied 34 patients with esophageal cancer and found that the eNO-changing ratio can be used as a classifier to predict SRP with a smaller average error rate (only 8%).…”
Section: Discussionsupporting
confidence: 54%
“…A total of 3/5 of these patients developed RP requiring steroid medication (6). McCurdy et al (20) and Guerrero et al (21) examined 28 patients with esophageal cancer and identified that a 1.5-fold increase in eNO exhibited 100% sensitivity and specificity for the prediction of RP (18,20). In another study by the same group, the ratio of eNO (the level at the end of RT/pre-RT level) was calculated for 50 lung or esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by the same group, the ratio of eNO (the level at the end of RT/pre-RT level) was calculated for 50 lung or esophageal cancer patients. A threshold of 1.4 could perfectly distinguish symptomatic and asymptomatic patients (21). In contrast, Enache et al (18) identified that although the specificity of a 10 ppb increase in eNO level was relatively specific (specificity, 83%) for predicting RP symptoms in lung cancer patients, the sensitivity was low (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors such as percentage of lung irradiated [14-16] and chemotherapy type [3,7,17] have been shown to affect occurrence and degree of RP. Another such factor, interstitial pneumonitis (IP) on pretreatment computed tomography (CT) scans, has been shown to predict an increased risk of symptomatic RP [18-20].…”
Section: Introductionsmentioning
confidence: 99%